2018
DOI: 10.1080/22423982.2018.1536252
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival of head and neck cancer patients in Greenland

Abstract: Previously, head and neck cancer (HNC) patients in Greenland have had significant diagnostic delay and poor survival rates. From 2005-2009 several initiatives have been made to ensure faster diagnosis and better survival. The aim of this study was to compare the prognosis before and after these initiatives were introduced.All Greenlandic patients diagnosed with HNC between 2005 and 2012 were included. Data were retrieved from medical records and national databases and compared with the period 1994-2003. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Laryngeal cancer had the highest ASIR among Faroese men while thyroid gland cancer had the highest ASIR among Faroese women. Similar findings are also confirmed in other studies [ 3 , 26 , 30 ]. The biggest difference between Faroese and Danish HNC patients was for men with oral cavity cancer and OPC with a noticeably higher ASIR for Danish male HNC patients.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Laryngeal cancer had the highest ASIR among Faroese men while thyroid gland cancer had the highest ASIR among Faroese women. Similar findings are also confirmed in other studies [ 3 , 26 , 30 ]. The biggest difference between Faroese and Danish HNC patients was for men with oral cavity cancer and OPC with a noticeably higher ASIR for Danish male HNC patients.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that the ASIR for all HNC was higher among men than women. Similar trends are seen in other Nordic studies [26][27][28][29][30]. Laryngeal cancer had the highest ASIR among Faroese men while thyroid gland cancer had the highest ASIR among Faroese women.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations